Uterine necrosis, infection, and subinvolution: complications observed after combined application of modified B-Lynch suture and vascular ligation. Issue 5 (May 2021) - Luo, Linfeng; Wan, Junhui; Chen, Xinping; Zhang, Huan; Zhang, Minjie; Chen, Qi
Compression sutures are primarily used to treat atonic postpartum hemorrhage. We herein describe three cases of selective arterial ligation combined with B-Lynch or modified B-Lynch suture for the treatment of intractable postpartum hemorrhage unresponsive to available conservative interventions. Three pregnant women underwent a cesarean section for a macrosomic fetus, fetal distress, and oligohydramnios, respectively. All three women developed intractable postpartum hemorrhage due to uterine atony with no chance of embolization therapy. B-Lynch or modified B-Lynch suture and additional selective arterial ligation were performed using braided absorbable suture. The first woman developed postoperative hematometra and infection without response to drainage and antibiotic therapy. Although laparoscopic exploration was performed to loosen the suture line and drain the hematometra and pyometra, the necrosis and infection could not be controlled. Subtotal hysterectomy was therefore conducted, and the necrotic uterine adnexa was removed. The other two women developed subinvolution of the uterus resulting in prolonged menstruation and amenorrhea, although the uterus was preserved and the bleeding was controlled. Modified B-Lynch suture combined with vascular ligation is an invaluable technique for women with severe intractable postpartum hemorrhage. However, it can lead to serious complications such as uterine necrosis, infection, and subinvolution.